Cocopeat Perlite Mixture as an Alternative for Rooted Cuttings Growth Medium of Impatiens hawkeri x platypetala in Indonesia - Shintiavira, Herni; Dewanti, Minangsari; Rachmawati, Fitri; Nurlaeni, Yati; Nurdina, Dani; Sadli, Sadli; Ariyantika, Safani; Kartikaningrum, Suskandari (Caraka Tani: Journal of Sustainable Agriculture, 2023)
Impatiens hawkeri x platypetala rooted cuttings are typically cultivated using rice husks as a substrate. However, due to the poor water-holding capacity of this medium, Impatiens grows slowly in this environment. A viable alternative is the cocopeat perlite mixture which has a better water-holding capacity compared to the rice husk. Currently, there is no sufficient information available regarding the best growth medium to improve the quality of I. hawkeri x platypetala rooted cuttings in Indonesia. Therefore, this study aimed to obtain the best medium for quality rooted cuttings I. hawkeri x platypetala. The method employed was a randomized complete block design with two factors. The first factor was the Impatiens varieties consisting of Impala Agrihorti, Imadata Agrihorti, and Lavender, while the second was the growth medium, comprised of four levels namely rice husk (control), as well as a mixture of cocopeat with 3%, 5% and 8% perlite. The result showed that there was no interaction between varieties and growth medium. The mixture of 3% perlite in cocopeat exhibited better outcomes compared to other treatments. This medium increased the number and length of roots, stem diameter, plant height, leaves thickness, leaves number and survival rate. Therefore, the addition of 3% perlite in cocopeat could replace the rice husk as a rooted cutting growth medium for I. hawkeri x platypetala.